Proteome profiling of extracellular vesicles-derived from hepatitis B virus-infected hepatocellular carcinoma cell lines identifies PDCD11 as a carrier of viral RNAs - Dey, Indrashish; Das, Anusmriti; Das, Subhas; Saha, Soham; Chowdhury, Abhijit; Datta, Simanti; Banerjee, Soma (Frontiers in Cell and Developmental Biology, 2025)
IntroductionHepatocellular carcinoma (HCC) is the ultimate result of long-term chronic hepatitis B. Molecular interactions among parenchymal, non-parenchymal, and immune cells in the liver tumor microenvironment (TME) influence the progression of the disease by sharing molecules such as protein, nucleic acids (DNA, coding and non-coding RNAs), lipids, and others through extracellular vesicles (EVs). This study has examined the influence of Hepatitis B virus (HBV) on the enrichment of proteins in the HCC cell-derived EVs and vice versa.MethodsEVs were isolated from conditioned media of stable HBV-containing HepG2.2.15 and HepG2-vector cells using kit and the quality was verified by Nano-particle tracking analysis (NTA) and immunoblotting with EV-specific antibody. Proteome analysis was performed in triplicate with the isolated EV-protein content using label-free LC-MS/MS technology and validated using HBV infected Huh7 and HepG2 cells. Various bioinformatics tools, transfection with Full-length (FL) HBV, anti-sense-oligo (ASO) treatment, immunoblotting, qRT-PCR, chromatin-immunoprecipitation (ChIP), cell proliferation, migration and spheroid formation assays were performed as required. Student’s t-test was performed for statistical analysis.ResultsProteome data analysis showed that HBV triggered accumulation of 3.4 times more proteins in the EVs-derived from HepG2.2.15 (2,293 proteins) compared to HepG2-vector cells (677 proteins). Differential expression (DE) analysis and subsequent validation with proteomics data of HBV-HCC liver tissue samples revealed enrichment of 103 commonly DE proteins in the EVs of HepG2.2.15 cells. These proteins mostly participated in DNA repair, RNA metabolism, and Golgi trafficking pathways, and these proteins were also overexpressed within cells in presence of HBV. Furthermore, protein-protein network and Hub gene analysis identified 10 key proteins that can interact with other proteins in the network. One of these hub proteins, programmed cell death protein 11 (PDCD11), has been identified as a carrier of HBV-RNA/DNA to the EVs. Depletion of PDCD11 limited the accumulation of HBV-RNAs (pre-genomic RNA, HBx, HBc, HBs mRNAs) and intact virions into the EVs. The FL-HBV genome was detected within EV-enriched virus core particles, which have the potential to infect naïve hepatocytes. Next, integrated transcription factor (TF)-mRNA-miRNA network analysis and validation revealed that TFDP1 transcriptionally upregulated PDCD11, along with other hub proteins, while miR-1-3p has been characterized to suppress their expressions. The binding of TFDP1 to the promoters of the hub genes was further confirmed by ChIP followed by qRT-PCR. Finally, depletion of TFDP1 using ASO and restoration of miR-1-3p in Huh7 cells restricted proliferation, migration, epithelial to mesenchymal transition, and stemness traits in HBV-infected HCC cells.ConclusionProteins enriched in the EVs-derived from HCC cells in presence of HBV may be further investigated to identify novel therapeutic targets within the TME of HBV-HCC. Our findings demonstrated the therapeutic potential of TFDP1-ASO and miR-1-3p, which could lead to new approaches in HBV-HCC treatment.